AN INVESTIGATION INTO ENGLISH VOCABUALRY LEANRING STRATEGIES USED BY 11TH GRADE STUDENTS AT MINH KHAI HIGH SCHOOL - Nguyễn, Hồng hạnh (2021)
This study investigated the vocabulary learning strategy used by 11th grade students at Minh Khai High School and reported the results of gender differences in the use of vocabulary learning strategy. In the current study, the strategies are studied through a survey including questionnaire administered to 253 students at 11th grade in Minh Khai High School and interviews among 8 students picked out from the participants. It was followed by calculating the descriptive statistics on Statistical Package for the Social Sciences software (SPSS) and running a T-test, the study tried to examine if there is any difference in the male and female use of these strategies or not. In addition, the results revealed the most and least frequent used vocabulary learning strategies by the respondents. The study observed “ taking notes in class” and “studying sounds of words” were the strategies which language learners most often use to find the meanings of new vocabulary items and “underlining initial letter” and “using semantic map” were the least frequently-used vocabulary learning strategies. Furthermore, the results showed that there are few strategies shared by male and female students compared with other previous studies. More importantly, considerable distinction between the way two genders use vocabulary learning strategy was demonstrated after a close analysis